2007
DOI: 10.1016/j.ajem.2007.02.027
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of intranasal fentanyl vs intravenous morphine for analgesia in the prehospital setting

Abstract: There was no significant difference in the effectiveness of INF and IVM for prehospital analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 24 publications
3
103
0
2
Order By: Relevance
“…Morphine was similar to buprenorphine (Weiss & Ritz, 1988 Level II) and pethidine (Nielsen et al, 1984 Level II) in terms of analgesia and adverse effects. IN fentanyl and IV morphine were equally effective in reducing acute cardiac chest pain during prehospital transfer (Rickard et al, 2007 Level II).…”
Section: Chaptermentioning
confidence: 99%
See 3 more Smart Citations
“…Morphine was similar to buprenorphine (Weiss & Ritz, 1988 Level II) and pethidine (Nielsen et al, 1984 Level II) in terms of analgesia and adverse effects. IN fentanyl and IV morphine were equally effective in reducing acute cardiac chest pain during prehospital transfer (Rickard et al, 2007 Level II).…”
Section: Chaptermentioning
confidence: 99%
“…and IV morphine were equally effective in reducing acute cardiac chest pain during prehospital transfer (Rickard et al, 2007 Level II). In a study of patients with post-traumatic thoracic pain, there was no difference in analgesia between nebulised morphine and morphine PCA (Fulda et al, 2005 Level II).…”
Section: For Details) In Fentanylmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that within 15 minutes of administration, only 50% of the patients experience pain control. [4,8,9] Therefore, despite noticeable strides, pain control in the ED is still an unresolved issue. [3,[1][2][3][4][5][6][7][8][9][10][11][12] Consequently, researchers have proposed other drug regimens to reduce MS consumption in the ED.…”
mentioning
confidence: 99%